Independent Anemia Care Monitoring Card Improves Iron Tablets Compliance and Hemoglobin - Rumintang, Baiq Iin; Halimatusyaadiah, St; Sundayani, Lina; Sulistianingsih, Apri (Universitas Aisyah Pringsewu, 2022)
Anemia is still a problem for pregnant women. One of the efforts for its management is compliance with the consumption of blood-added tablets (TTD). The self-monitoring card for anemia care is an easy intervention to help mothers improve adherence to iron tablets consumption. This study aims to determine the comparison of the effectiveness of the use of the Mandiri Monitoring Card “Caring for Anemia on the adherence of pregnant women to take TTD (Mixed-Method Study in Mataram City and Pringsewu Regency). This study uses a mixed-method design with a sequential model approach using quantitative methods (quasi-experimental studies) followed by qualitative (structured interviews). Research subjects in the quantitative method consisted of 30 people each in the intervention group (Mataram City and Pringsewu Regency) and 30 each in the control group (Mataram City and Pringsewu Regency). Qualitative research of five people each for Mataram City and Pringsewu Regency. Data analysis used unpaired T-test as well as transcription and categorization analysis. The results were obtained. The results of the test at the end of the study showed that there was a significant difference between the intervention group and the control group on the adherence to TTD consumption in Mataram City and Pringsewu Regency (P less than 0.05). There was no significant difference in hemoglobin levels of pregnant women in the intervention group compared to the control group in both Mataram City and Pringsewu Regency (P-Value more than 0.05). In the control group, the increase in hemoglobin levels was more positive in two places. In contrast to the intervention group in Mataram City which showed almost no increase in hemoglobin levels in pregnant women (-0.007±1.08), compared to the intervention group in Pringsewu District (0.37±0.72)). This study shows that the monitoring card prevents pregnant women from experiencing hemodilution at the peak of pregnancy so that their hemoglobin does not decrease.Anemia masih menjadi masalah bagi ibu hamil. Salah satu upaya untuk penatalaksanaanya adalah dengan kepatuhan konsumsi tablet tambah darah (TTD). Kartu pantau mandiri peduli anemia sebuah intervensi yang mudah untuk membantu ibu meningkatkan kepatuhan konsumsi TTD. Penelitian ini bertujuan untuk mengetahui Perbandingan Efektifitas Penggunaan Kartu Pantau Mandiri “Peduli Anemia terhadap kepatuhan ibu hamil minum TTD (Studi Mixed Method di Kota Mataram dan Kabupaten Pringsewu). Penelitian ini menggunakan desain mixed method dengan pendekatan model sequential dengan menggunakan metode quantitative (quasi experimental studies) dilanjutkan qualitative (wawancara terstruktur). Subjek penelitian pada metode kuantitatif terdiri dari masing-masing 30 orang kelompok intervensi (Kota Mataram dan Kabupaten Pringsewu) dan masing masing 30 orang kelompok control (kota mataram dan Kabupaten Pringsewu). Penelitian Kualitatif masing-masing lima orang untuk Kota Mataram dan Kabupaten Pringsewu. Analsis data menggunakan uji T tidak berpasangan serta analisis transkripsi dan kategorisasi. Hasil penelitian didapatkan. Hasil uji pada akhir penelitian menunjukkan bahwa ada perbedaan bermakna kelompok intervensi dan kelompok control pada kepatuhan konsumsi TTD pada Kota Mataram dan Kabupaten Pringsewu (P less than 0,05). Tidak ada perbedaan bermakna kadar hemoglobin ibu hamil pada kelompok intervensi dibanding kelompok control baik di Kota Mataram Maupun Kabupaten Pringsewu (P Value more than 0,05). Pada kelompok control peningkatan kadar hemoglobin lebih kea rah positif di dua tempat. Berbeda dengan kelompok intervensi di Kota Mataram yang menunjukkan hamper tidak ada peningkatan kadar hemoglobin pada Ibu Hamil (-0,007±1,08) , dibandingkan .kelompok intervensi Kabupaten Pringsewu (0,37±0,72)). Pada studi ini menunjukkan bahwa kartu pantau membuat ibu hamil tidak mengalami hemodilusi di puncak kehamilan sehingga hemoglobin tidak menurun.